Building Investment Compliance Through LKPM Development: Analysis of The Performance DPMPTSP of Palembang - Angga Afriansyah; Januar Eko Aryansah (Jurnal Studi Sosial dan Politik, 2025)
This study aims to analyze employee performance in fostering the reporting of Investment Activity Reports (LKPM) for business actors at the Palembang City Investment and One-Stop Integrated Services Agency (DPMPTSP). The UKPM is an important instrument for monitoring investment realization and business actors' compliance with regulations. This study used qualitative methods using interview, observation, and document analysis techniques. The results show that coaching activities are influenced by employee work quality, adherence to deadlines, and information technology support. Although the level of business actors' compliance in reporting LKPM has increased, obstacles such as lack of socialization and limited staff remain. Therefore, strategies are needed to increase employee capacity, optimize technology utilization, and improve coordination with business actors to ensure smooth and transparent investment reporting.